Implementasi Kebijakan Remunerasi Berdasarkan Permendagri Nomor 79 Tahun 2018 Di Rsud Salewangang Maros - Fitri Adhicahya; Reza Aril Ahri; Arman (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Remuneration is a method of motivating someone to improve their performance. Remuneration is a form of positive reinforcement, but if given correctly and wisely it can be a motivational tool. Provisions related to remuneration in regional regulations must be adjusted to Permendagri 79/2018 and the legal basis for BLUD remuneration regulations and procedures for establishing regulations for determining the remuneration of BLUD employees. The general purpose of this study is to determine the implementation of Regulation No. 79 of 2018 concerning Remuneration Policy at Salewangang Maros Regional Hospital. While the specific objective is to determine the implementation of Permendagri No. 79 of 2018 concerning Remuneration Policy at Salewangang Maros Regional Hospital. Method: The research method used is a qualitative research method, namely the research method used to examine the condition of a natural object, (as opposed to an experiment), where the researcher is the key instrument, the data collection technique is done by triangulation (combined), data analysis is inductive, and qualitative research results emphasize meaning rather than generalization. Results: The results showed that the remuneration was regulated by a regional head regulation based on the leader's recommendation (Director of Salewangang Maros Hospital). This is in accordance with Article 24 paragraph (1) Permendagri Number 79 of 2018. Provision of remuneration is in accordance with Permendagri Number 79 of 2018 as outlined in Perbub Maros No. 5 of 2019. Remuneration is given in accordance with the Maros Ministerial Regulation which uses an indexing system. The indexing itself refers to the indicators of remuneration assessment in the Permendagri, although in practice there are those that have not met the requirements (indicators), among others, the provision of services has not taken into account performance achievement indicators (individual performance indicators and unit performance indicators). Conclusion: Based on the results of the research and discussion, the researcher can conclude that: Remuneration is regulated by a regional head regulation based on the leader's recommendation (Director of Salewangang Maros Regional Hospital). This is in accordance with Article 24 paragraph (1) Permendagri Number 79 of 2018. Remuneration is in accordance with Permendagri Number 79 of 2018 as outlined in the Regulation of the Minister of Home Affairs No. 5 of 2019. Remuneration is given in accordance with the Maros Regulation, which uses an indexing system. The indexing itself refers to the indicators of remuneration assessment in the Permendagri, although in practice there are those that have not met the requirements (indicators), among others, the provision of services has not taken into account performance achievement indicators (individual performance indicators and unit performance indicators).